2009
DOI: 10.1002/jhm.449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improvement efforts on glycemic control and hypoglycemia at a University Medical Center

Abstract: BACKGROUND:Great emphasis is placed on optimizing treatment of hospitalized patients with diabetes and hyperglycemia.OBJECTIVE:This study was conducted to determine if the application of hospital‐wide insulin order sets improved inpatient safety by reducing the number of actual hypoglycemic and hyperglycemic events and increasing at‐target blood glucose.DESIGN:A retrospective chart review was conducted of hypoglycemic and hyperglycemic events and at‐target blood glucose occurring before and after institution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Multiple glycemic management educational interventions, including case-based learning modules and lectures for nursing and providers 59 and dietitians, were implemented to improve insulin-prescribing practices and glycemic outcomes.…”
Section: Hospitalwide Policies Development and Implementationmentioning
confidence: 99%
“…Multiple glycemic management educational interventions, including case-based learning modules and lectures for nursing and providers 59 and dietitians, were implemented to improve insulin-prescribing practices and glycemic outcomes.…”
Section: Hospitalwide Policies Development and Implementationmentioning
confidence: 99%
“…Among 13 studies that evaluated glucometrics, 5 (~40%) showed reductions in hypoglycemia rates and 9 (~70%) showed reductions in hyperglycemia rates. Among the 9 studies showing a reduction in hyperglycemia rates, there was an accompanying increase in hypoglycemia rates in 2 studies 69,70 (~20%), a decrease in two studies 71,72 (~20%), and no change in 5 studies 7377 (~60%). Generally, favorable changes in insulin-prescribing practices were demonstrated, with increased use of basal-bolus insulin in place of prolonged use of sliding-scale monotherapy.…”
Section: Parallels In Functions Of Infection Control and Glucose Manamentioning
confidence: 98%
“…A well designed order set facilitates individualization of patient care. Guidelines may be appended to or embedded within order sets, together with references to supportive medical literature (Donaldson et al 2006;Hermayer et al, 2009;Lee et al 2008;Maynard et al, 2009;Schnipper et al, 2010;Trujillo et al, 2008;Wexler et al, 2010). Protocols executed through order sets were thought to reduce medical errors, improve safety, and increase adherence to those guidelines that were supported by medical evidence.…”
Section: Algorithms For Subcutaneous Insulinmentioning
confidence: 99%